Формування історичних поглядів Лесі Українки - Лук’янчук, Лідія; Lukianchuk, Lidiia (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття присвячена проблемам формування історичних поглядів Лесі Українки та значенню впливу на її науково-громадянську позицію матері Олени Пчілки й дядька М. П. Драгоманова, які були порадниками та вчителями протягом усього життя поетеси. Історію дружніх стосунків цих визначних діячів української культури та їх вплив на формування характеру, творчості, історичних поглядів, еволюцію світогляду простежено на аналізі творів пись- менниці та матеріалах епістолярної спадщини. The article is devoted to problems of formation of historical views of Lesia Ukrainka and value the influence of scientific and civic position of her mother Olena Pchilka and her uncle M. P. Drahomanov. who were the advisers and teachers throughout the life of the poet. However, the author attempts to illuminate the reasons of activation of creative and social activities of Lesіa Ukrainka in the late nineteenth – early twentieth century given the rise of the revolutionary movement in Ukraine and Russia. Historical evolution of views of Larуsa Kosach led to the rapprochement with the revolutionary circles and organisations, including the social-democratic direction. The article raises the question of the appeal of the writer to the historical subject as a way of realization of their aspirations for the solution of universal problems and historical conflicts. But Lesіa Ukrainka studied the history of the world in two consecutive areas, the search for the required theme for the free expression of the Ukrainian reality and how the scientific study of the historical era in which she made reference. Due to analysis of the works of the writer and the materials of the epistolary heritage was traced back the history of friendly relations of these prominent figures of Ukrainian culture and influence on their character formation, creation, historical views, evolution of worldview.
The Formation of Historical Views of Lesia Ukrainka
Keywords: історія; М. Драгоманов; матеріалізм; марксизм; національна ідея; прометеїзм; Олена Пчілка; світогляд; history; Drahomanov; materialism; Marxism; national idea; prometheism; O. Pchilka; worldview